2015
DOI: 10.1371/journal.pone.0143298
|View full text |Cite
|
Sign up to set email alerts
|

Association between BMP15 Gene Polymorphism and Reproduction Traits and Its Tissues Expression Characteristics in Chicken

Abstract: BMP15 (Bone morphogenetic protein 15) is an oocyte-secreted growth factor required for ovarian follicle development and ovulation in mammals, but its effects on reproduction in chickens are unclear. In this study, the association between BMP15 polymorphisms and reproduction traits were analyzed, and its expression characteristics in different tissues were explored in LaiWu Black chickens. Three single nucleotide polymorphisms (SNPs) were identified in four hundred LaiWu Black chickens. One SNP (NC_006091.3:g.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The correlation analysis showed that the polymorphic loci of g310 A > g, g181 A > T, and g159 C > T were all correlated with the number of eggs in Beijing-You chicken population of different weeks (P < 0.05) [10]. Han HX et al (2015) studied the relationship between BMP15 gene polymorphism and reproductive traits of LaiWu Black chicken and identi ed three single nucleotide polymorphisms (SNPs) [11]. Sex hormone regulation also affects the development of sex organs and egg production.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation analysis showed that the polymorphic loci of g310 A > g, g181 A > T, and g159 C > T were all correlated with the number of eggs in Beijing-You chicken population of different weeks (P < 0.05) [10]. Han HX et al (2015) studied the relationship between BMP15 gene polymorphism and reproductive traits of LaiWu Black chicken and identi ed three single nucleotide polymorphisms (SNPs) [11]. Sex hormone regulation also affects the development of sex organs and egg production.…”
Section: Introductionmentioning
confidence: 99%
“…nuclear receptor subfamily 4 group A member 1 ( nr4a1 ; Abdou et al, 2013) and retinoic acid receptor, gamma b ( rargb ), closely mapped in LG22. Other important genes related to gonad development, bone morphogenetic protein 15 ( bmp15; Han et al, 2015) and cytochrome P450, family 26, subfamily b, polypeptide 1 ( cyp26b1 ; Saba et al, 2014) were found in LG16, while the estrogen receptor 2b gene ( esr2b ; Delalande et al, 2015) in zebrafish LG13.…”
Section: Resultsmentioning
confidence: 99%
“…Based on multiple previous reports [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], we have chosen 14 characteristic SNP markers strongly associated with growth traits or carcass traits (P < 0.05) including rs13687128, rs317360945, rs14734533, rs314127605, NC_ 006092.4: g.25657391 T > A, NT_464126.1: g.66916G > A, rs314901473, rs316142388, rs314403820, rs14202565, rs16438236, rs13939265, rs15620544, rs16434462 and 14 characteristic SNP markers with strongly association with egg production traits (P < 0.05) including NC_006127.4: g.24021190G > A, rs16349546, NC_006096.4: g22545152 G > C, rs16486559, rs317328077, rs14714701, rs14085822, rs13905010, rs15602813, rs14491030, rs14699480, rs14652932, rs315420959 and rs313187645 for genotype frequency analysis. The specific information of the SNP markers is given together with their genetic background and corresponding traits in Tables 1 and 2.…”
Section: Selection and Summary Of 28 Snp Markersmentioning
confidence: 99%
“…To characterize the genetic variations and genetic relationships among different populations using DNA markers, a total of 28 identified SNP markers, including 14 growth or carcass traits associated loci and 14 egg laying related genome positions, were selected from the previous reports [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. By using the MassArray technology, an Agena Bioscience MassARRAY System which is capable of efficiently genotyping tens to hundreds of SNPs with high accuracy, we detected the genotype frequency distributions of the 28 SNP markers in seven populations including four lowly selected as well as one moderately selected Sichuan native chicken populations, one commercial broiler line and one commercial layer line [34,35].…”
Section: Introductionmentioning
confidence: 99%